Chapter International Standardization of FTV - Tanimoto, Masayuki (Proceedings e report, 2018)
FTV (Free-viewpoint Television) is visual media that transmits all ray information of a 3D space and enables immersive 3D viewing. The international standardization of FTV has been conducted in MPEG. The first phase of FTV is multiview video coding (MVC), and the second phase is 3D video (3DV). The third phase of FTV is MPEG-FTV, which targets revolutionized viewing of 3D scenes via super multiview, free navigation, and 360-degree 3D. After the success of exploration experiments and Call for Evidence, MPEG-FTV moved MPEG Immersive project (MPEG-I), where it is in charge of video part as MPEG-I Visual. MPEG-I will create standards for immersive audio-visual services.